Dakwah Digital: Transformasi Komunikasi Politik Ke Profetik - Rizal, Hadi Muhammad; Hirzi, Azis Taufik; Gani, Rita (FASTABIQ: JURNAL STUDI ISLAM, 2024)
The development of technology has experienced rapid growth and has influenced all aspects of life, including the economy, politics, arts and culture, education, and religion The Digital Village Program is an effort to spread awareness in the digital realm by the provincial government of West Java, aimed at developing the existing potential in villages and empowering rural communities to actively contribute to enhancing their capabilities This research aims to examine the pattern of political communication transformation with empowerment values for overall village progress in West Java. The research method used in this study is qualitative with a case study approach The paradigm employed is constructivism, and data collection techniques include interviews, observations, literature study, and document analysis The theories utilized are Social Construction and Symbolic Interactionism The research findings indicate that digital preaching serves as a means of communication interaction between the government and the public, and it also becomes a channel for political communication Thus, the pattern of political communication in West Java is new and unique in Indonesia. Keywords: Digital Da'wah; Political communication;  Prophetic communication .